Kevin Hart [videorecording (DVD)] : I'm a grown little man - Hart, Kevin, 1979- (Image Entertainment, 2012)
I'm a grown little man: Kevin Hart electrifies the audience with his clever, animated style of comedy in this hilarious sold out stand-up performance.